Pengaruh Perbedaan Warna Cahaya Terhadap Pertumbuhan Kultur Spirulina sp. [ The Effect Of Light Colour To Growth Culture Of Spirullina sp. ] - Rahayu Kusdarwati; Reista Herwiyanti Bustaman; Muhammad Arief (Jurnal Ilmiah Perikanan dan Kelautan, 2011)
Abstract Spirulina sp. is a microalgae that has spread widely, and can live in brackish waters, marine and freshwater. Spirulina is often the dominant species and can cause bloom (Ciferri, 1983 in Hu, 2004). Spirulina sp. have the ability to photosynthesize and convert light energy into chemical energy in the form of carbohydrates. The best environmental conditions for growth are in areas rich in sunlight, rainfall is, rich in carbon dioxide and temperature in the range of 25-35 ° C and pH ranging from 7.2 to 9.5. Spirulina sp. able to survive at salinity between 20-70 ppt, pH between 9 - 11 (Ciferri, 1983 in Richmond, 1986). This study aimed to know To know the color of light affect the growth of Spirulina sp. and the light color is best in promoting the growth of Spirulina sp. Effect of different colors of light can affect the growth of Spirulina sp. Methods The study is an experiment with the experimental design used was CRD (Completely Randomized Design) with five treatments and three replications with different colors of light that is A (white), B (green), C (blue), D (red), E (yellow). The color of light have different wavelengths, absorption by the different pigments and different penetration capabilities.